"Being in-Between": Spouses That Cohabit With and Provide Care for Their Partners in Nursing Homes. (April 2020) - Torgé, Cristina Joy
It is increasingly possible for couples with differing care needs to move to nursing homes together. To our knowledge, this is the first study about spousal caregiving in this context. This study explores spouse and staff experiences when relatively healthy spouses cohabit with and provide care to their partners in Swedish nursing homes. The overarching theme, "being in-between, " reflects the spouse's overlapping role transition and the staff's unfamiliarity with the spouse's role. The spouses are both "insiders" and "outsiders" and are torn between maintaining and letting go of caregiving. Meanwhile, the staff express concern about the spouse's need for respite yet being constantly present, and struggle to balance the staff's and the spouse's control of the caregiving situation. This article provides insight into the challenges experienced by spouses who accompany their partners to residential care and how to best support them in this unfamiliar role.